To etch or not to etch, Part II: On the hydrophobic-rich content and fatigue strength of universal adhesives. Issue 8 (August 2022) - Stape, Thiago Henrique Scarabello; Viita-aho, Tapio; Sezinando, Ana; Seseogullari-Dirihan, Roda; Eleftheriadi, Eirini; Mutluay, Murat; Tezvergil-Mutluay, Arzu
Abstract: Objective: To determine whether smear layer management, via conservative etching protocols, and the hydrophobic-rich content of hybrid layers would affect the fatigue strength of resin-dentin interfaces. Methods: Bar-shaped dentin beams obtained from sound third molars were wet-polished for 30 s. Dentin was etched with 32 % ortho-phosphoric acid for 3 or 15 s, 10 % meta-phosphoric acid for 15 s or by a prime-and-rinse application using a mild universal adhesive (Scotchbond Universal, 3M ESPE). Self-etch application served as control. Coating was performed with a solvent-free bisGMA-based resin. Composite buildups were made with a nanofilled composite. Resin-dentin beams with twin-bonded interfaces were sectioned and stored in deionized water for 24 h at 37 ℃ before 4-point flexural quasi-static monotonic testing (n = 16). Stress-life fatigue behavior was evaluated under cyclic loading (n = 35) by the staircase method at 4 Hz. The tension side of cyclic-loaded unfractured beams were evaluated under SEM, along with the micro-morphology of etched dentin surfaces. Monotonic data was analyzed by two-way ANOVA followed by the Tukey Test and cyclic-loaded data by Kruskal-Wallis on Ranks (α = 0.05). Results: Etching protocols and higher hydrophobic-rich content produced significantly higher fatigue life distributions ( p  < 0.05). Dentin demineralization was ranked as OPA 15 s > MPA 15 s > OPA 3 s > P + R > SE. Less aggressive etching and coating reduced crack formation at hybrid layers. Significance: Current oversimplification trends in resin-dentin bonding constitute a trade-off between hybridization quality and easier adhesive handling. Controlled dentin etching and increasing the hydrophobic-rich content of hybrid layers may be necessary to extend the longevity of mild universal adhesives. Highlights: Monotonic test setups may fail to identify differences between bonding protocols. Fatigue testing is a valuable method to assess resin-dentin interfaces. Smear layer removal extends the durability of mild universal adhesives. Higher hydrophobic content in hybrid layers increases fatigue strengths. Hydrophobic-rich coating reduces bonding variability of mild universal adhesives.